COMPARATIVE ANALYSIS OF LOSATAN AND ENALAPRIL ANTIHYPERTENSIVE EFFICACY (ELLA TRIAL) - N. M. Chihladze; O. A. Sivakova; H. F. Samedova; G. N. Litonova; E. B. Yarovaya; I. E. Chazova (Рациональная фармакотерапия в кардиологии)
Aim. To compare antihypertensive efficacy of АТ1 receptors blocker (losartan) and ACE inhibitor (enalapril), including their combinations with hydrochlorothiazide.Material and methods. 60 patients (30-65 y.o.) with arterial hypertension (HT) of stages 1-3 were involved in 12-week opened comparative randomized study. Patients of group-I (n=30) received losartan, patients of group-II (n=30) - enalapril. Blood pressure (BP) changes assessed on the basis of clinical measurements and ambulatory monitoring. Microalbuminuria (MAU) levels, plasma aldosterone levels and plasma renin activity were estimated.Results. Target BP levels were reached in 76,6% of patients in group-I and in 73,3% of patients in group-II. Among patients with moderate HT of stage 2 (n=50) target BP levels were reached in 96% of patients in group-I and in 72% of patients in group-II. Patients of both groups had positive changes in BP levels according to ambulatory BP monitoring. Significant reduction in MAU level and uric acid plasma concentrations were observed.Conclusion. Losartan (Losap, Zentiva) and losartan combination with hydrochlorothiazide (Losap-plus, Zentiva) demonstrated antihypertensive efficacy comparable with this of enalapril as well as nephroprotective features.